An Applied Approach to the Examination of Urban Acoustic Comfort: The Soundscape Concept - Statistical Analysis - Ozcevik, Asli; Can, Zerhan Yuksel; Gurbuz, Huseyin; Acar, Ilgin Poyraz (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2014)
A wide-ranging study was conducted in order to develop an applied soundscape approach for the evaluation, conservation and rehabilitation of acoustic comfort in urban areas. The steps taken in developing the approach proposal were; deriving objective and subjective evaluations of the sound environment via field and laboratory studies, statistically analysing the data, and correlating the results. Field studies concerning urban acoustic comfort are time-consuming, and the aim of this research was to investigate how the processes and the steps involved (obtaining, gathering, arranging and archiving sound environment data) may be accelerated and made more systematic in order to reduce the time spent on fieldwork, and benefit the practical application of findings. The aim of this paper is to explain the steps taken in the statistical analysis of the study. Therefore, using the data from field and laboratory studies, 1) comparisons were made between the on site questionnaire survey and listening tests in laboratory, 2) variance and t-test analyses were conducted between the semantic differential test on site and the jury test in the laboratory, and 3) a simple regression analysis was made between the tests on two different environments and sound quality metrics.
Keywords: Statistical analysis; soundscape; urban acoustic comfort; Architecture